If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -48 = 2x + -128 Reorder the terms: -48 + -8x = 2x + -128 Reorder the terms: -48 + -8x = -128 + 2x Solving -48 + -8x = -128 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -48 + -8x + -2x = -128 + 2x + -2x Combine like terms: -8x + -2x = -10x -48 + -10x = -128 + 2x + -2x Combine like terms: 2x + -2x = 0 -48 + -10x = -128 + 0 -48 + -10x = -128 Add '48' to each side of the equation. -48 + 48 + -10x = -128 + 48 Combine like terms: -48 + 48 = 0 0 + -10x = -128 + 48 -10x = -128 + 48 Combine like terms: -128 + 48 = -80 -10x = -80 Divide each side by '-10'. x = 8 Simplifying x = 8
| -10k=1720 | | K+-36=36 | | 6-(6x+5x)=13 | | K+24=-36 | | 5.6+2.9-1.3=y+12.9-6.3 | | N+-15=-36 | | -2p=43 | | 5.2+x=31 | | X+-14=27 | | 5.2+x=41 | | 2x-5x-13=-3x+7-13 | | 3n^2+5n-2= | | (2x+1)(4x-1)=32 | | M+32=-40 | | H-12.6-4.5=4.8+19.6 | | M+12=-12 | | y=3x^4-6x^2+5 | | M+-6=-5 | | C+20=-10 | | (2x-9)(x+7)=0 | | 15+27-23=d-32 | | 92=2(x+x+4) | | 5[-3(3x+5)+3(5x-3)]= | | -5v+6=-19 | | 2y^2+x^2-4y-18=0 | | W+-6=10 | | K+10=30 | | H(t)=-16t^2+48t+50 | | 5+8p=-147 | | t^3-4t^2+7t+3=0 | | 5+8-p=-147 | | M+-10=10 |